RANCANG BANGUN PROTOTYPE PADA APLIKASI E-COMMERCE BERBASIS WAP - Iman Dhermawan; Rendra Bomantara (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2021)
Entering the era of globalization, the use of information technology in all areas of daily life cannot be avoided. There are at least two technologies that have developed rapidly in the last few years for the lives of millions of people, namely the internet and cell phones. By combining these two technologies, technology is created that makes it possible to access information that does not depend on the information source and location of access, namely WAP. Along with the development of the combination of the two technologies, several business owners began to use it. One of them is the Podomoro Notebook Store, which is located at SCC Plaza Simpang Lima, Fl. V No. 62 Semarang which is engaged in selling notebooks is trying to use it. There are several things that might encourage this application to be used, including in terms of notebook sales. The absence of an application regarding ordering goods online is also an obstacle for the shop. The solution to solving the problem of this case is to create a wap-based information system for ordering goods. With the wap-based information system, it is hoped that it will help a little in terms of sales and this system can help to order goods online.